2019
DOI: 10.1111/jocn.14992
|View full text |Cite
|
Sign up to set email alerts
|

Disability, emotional distress and well‐being among patients with lumbar spondylolisthesis

Abstract: Aim and objective To explore the disability, emotional distress and well‐being of patients with lumbar spondylolisthesis. Background Few studies have investigated the correlations between disability, emotional distress and well‐being of patients with lumbar spondylolisthesis. Design This study used a cross‐sectional research design. Methods Participants were 133 patients aged over 50 years who were experiencing lumbar spondylolisthesis. The research instruments included a demographic information questionnaire;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Specifically, studies have found that social support, friendships with other people with disabilities, adaptability, and self-efficacy are all linked to higher well-being in clinical populations (Börsbo et al, 2010; Silverman et al, 2017). In contrast, experiencing disability discrimination and higher levels of anxiety have been negatively associated with well-being (Hackett et al, 2020; Hsu et al, 2019). As such, psychosocial factors may be critical to consider when examining well-being among individuals with Charcot–Marie–Tooth (CMT) disease.…”
Section: Factors That Promote Well-beingmentioning
confidence: 99%
“…Specifically, studies have found that social support, friendships with other people with disabilities, adaptability, and self-efficacy are all linked to higher well-being in clinical populations (Börsbo et al, 2010; Silverman et al, 2017). In contrast, experiencing disability discrimination and higher levels of anxiety have been negatively associated with well-being (Hackett et al, 2020; Hsu et al, 2019). As such, psychosocial factors may be critical to consider when examining well-being among individuals with Charcot–Marie–Tooth (CMT) disease.…”
Section: Factors That Promote Well-beingmentioning
confidence: 99%
“…This assumption is linked to aging, heredity, the impact of the activity, and occupation which are key factors in the assessment procedures of functional abilities (Sharma et al, 2015;Duruöz et al, 2013). Studies have shown significant relationships between age, gender, occupation, and the development of degenerative spondylolisthesis (Kamal & Rouhi, 2019& Hsu et al, 2019.…”
Section: Introductionmentioning
confidence: 99%